The Relation between Economic Growth and Oil Production in the Gulf Cooperation Countries: Panel ARDL Approach - Hafsi, Rachid; Dadene, Abdelghafour; Guennoun, Abdelhak (International Journal of Energy Economics and Policy, 2021)
This study investigated the impact of oil Petroleum production on economic growth in the Gulf Cooperation Council countries using panel autoregressive distributed lag model covering the period from 1960 to 2018. The results indicated that oil Petroleum production have significant positive impact on economic growth in both the long-run and the short-run period, also results show that variables are Co integrated by using the pool mean group (PMG) method. Panel Causality Test indicates that there is a causal relationship between Oil production and economic growth. There exists unidirectional causality running from economic growth (GDP) to petroleum production (PP). Keywords: Economic growth, Petroleum production, CCG countries, Panel co-integration, Panel causality JEL Classifications: C01, Q40, Q43 DOI: https://doi.org/10.32479/ijeep.11048